A systematic literature review of blockchain-based applications: Current status, classification and open issues - Casino, Fran; Dasaklis, Thomas K.; Patsakis, Constantinos (Telematics and informatics, 2019)
•A systematic review of blockchain-based applications across multiple domains.•We investigate the current state of blockchain technology.•We identify the characteristics that can revolutionise “business-as-usual” practices.•We provide a framework to determine the fitness of blockchain per application. This work provides a systematic literature review of blockchain-based applications across multiple domains. The aim is to investigate the current state of blockchain technology and its applications and to highlight how specific characteristics of this disruptive technology can revolutionise “business-as-usual” practices. To this end, the theoretical underpinnings of numerous research papers published in high ranked scientific journals during the last decade, along with several reports from grey literature as a means of streamlining our assessment and capturing the continuously expanding blockchain domain, are included in this review. Based on a structured, systematic review and thematic content analysis of the discovered literature, we present a comprehensive classification of blockchain-enabled applications across diverse sectors such as supply chain, business, healthcare, IoT, privacy, and data management, and we establish key themes, trends and emerging areas for research. We also point to the shortcomings identified in the relevant literature, particularly limitations the blockchain technology presents and how these limitations spawn across different sectors and industries. Building on these findings, we identify various research gaps and future exploratory directions that are anticipated to be of significant value both for academics and practitioners.